Transport properties of a molecular quantum dot coupled to one-dimensional correlated electrons - Maier, Stefan; Komnik, Andreas (Physical review. B, Condensed matter and materials physics, 2010)
We analyze the transport properties of a quantum dot with a harmonic degree of freedom (Holstein phonon) coupled to interacting one-dimensional metallic leads. Using Tomonaga-Luttinger model to describe the interacting leads we construct the generating function of the full counting statistics for a specific constellation of system parameters and give explicit expression for the cumulant generating function. In the resonant case we find the lowest order correction to the current to be negative and divergent when source-drain voltage approaches the phonon frequency. Via a diagram resummation procedure we show, that these divergencies can be repealed. On the contrary, in the off-resonant case the lowest order correction remains finite. This effect can be traced back to the strongly nonmonotonic behavior of the bare transmission coefficient (without phonon) with respect to the dot level energy. We calculate corrections to the noise power as well and discuss possible experimental implications of this phenomenon.